Thermodynamics of strain-induced crystallization in filled natural rubber under uni- and biaxial loadings, Part I: Complete energetic characterization and crystallinity evaluation. (February 2022) - Khiêm, V.N.; Le Cam, J.-B.; Charlès, S.; Itskov, M.
Abstract: The present paper provides the first full thermo-mechanical characterization of a crystallizing filled natural rubber under uniaxial and biaxial loadings. During the mechanical tests, the temperature was measured by using infrared thermography and processed by means of the heat diffusion equation for determining the corresponding heat power density. The intrinsic dissipation due to viscosity and stress softening are evaluated under cyclic loading by the energy balance. Energy contributions to the hysteresis loop converted into heat and stored in the material are distinguished. The heat power density is also used to evaluate the strain-induced crystallinity. This analysis provides new results on the energetic behavior of filled natural rubber. Accordingly, crystallization takes place under high biaxiality levels, close to the equibiaxial loading condition, while multiaxiality influences the crystallization onset. These experimental results are used in the second part of the present paper for a physically based modeling of the complex behavior of filled natural rubbers.